PROFESSIONAL COMPETENCE OF THE FUTURE FOREIGN LANGUAGE TEACHERS AS AN INDICATOR HIS PROFESSIONALISM - O.V. Pakhomova (Academy of Cognitive and Natural Sciences, 2022)
This article considers the problem of the professional competence of a teacher in the context of the training of future teachers for teaching and upbringing activities.